State Recognition and Islamic Legal Authority: Repositioning the Mufti Institution in Greece - Apostolos G. Paralikas; Anna Boumpa (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2026)
This article analyses the transformation of Islamic personal status law for the Muslim minority in Thrace within the Greek legal order. Historically grounded in obligations under the Treaty of Lausanne, Sharia jurisdiction functioned as a state-administered system that generated persistent tensions between minority protection, constitutional equality, and individual autonomy. Through an integrated doctrinal approach combining treaty interpretation, statutory analysis, and jurisprudential review—centred on the landmark judgment in Molla Sali v. Greece before the European Court of Human Rights—the study demonstrates how supranational human rights scrutiny destabilised identity-based legal pluralism. The Court’s rejection of compulsory Sharia inheritance rules prompted legislative reforms in 2018 and 2022 that redefined the Mufti’s jurisdiction as conditional upon explicit consent and enhanced judicial oversight. The article argues that these reforms do not abolish religious jurisdiction but recalibrate it within a constitutional framework centred on verified voluntariness, equality, and procedural safeguards. The Greek experience thus illustrates a model of conditional legal pluralism in which religious adjudication remains legitimate only when embedded within effective state supervision and individual choice. By situating the Greek case within broader European human rights debates, the study clarifies a normative threshold for reconciling minority protection with constitutional democracy.